The Effects of Hormonal Therapy on Quality of Life in Prostate Cancer - ÇAM, HAYDAR KAMİL (GALENOS YAYINCILIK, 2015)
The incidence of prostate cancer is dramatically increasing. Androgen blockade is widely utilized in the management of metastatic and locally advanced prostate cancer. Despite the benefits of this treatment, side effects and shortcoming of quality of life (QoL) constitute the major drawbacks of the hormonal treatment. The proper approach includes precautions in order to provide a lesser impairment in QoL. Therefore, physicians should consider the complications of hormonal treatment and should inform their patients. This review was prepared to point out the QoL changes regarding the hormonal treatment.
Keywords: Prostate cancer; quality of life; hormonal therapy; ANDROGEN-DEPRIVATION THERAPY; RANDOMIZED CONTROLLED-TRIAL; BICALUTAMIDE 150 MG; ZOLEDRONIC ACID; FOLLOW-UP; BONE LOSS; MEN; SUPPRESSION; RADIOTHERAPY; CASTRATION